2017
DOI: 10.1186/s12891-017-1878-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of atypical subtrochanteric and femoral fracture related to bisphosphonates use in osteoporotic patients with or without teriparatide treatment

Abstract: BackgroundAtypical subtrochanteric fracture and femoral fracture have been considered to be rare complications related to long-term bisphosphonates use. A reduced bone turnover rate may lead to delayed bone healing. Limited data have revealed that teriparatide treatment may reverse the effect of bisphosphonates and be effective in bone healing.MethodsWe reviewed patients with atypical subtrochanteric and femoral fracture related to bisphosphonates use between January 2008 and December 2014. Thirteen female pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…All TPTD group showed fast er healing time (5.4±1.5 vs. 8.6±4.7 months; P =0.012), and low frequency of delayed healing or nonunion ( P =0.012) [ 61 ]. Yeh et al [ 62 ] also retrospectively examined 13 female patients with a total of 16 AFFs that all treated with an intramedullary fixation and divided into 2 groups (8 AFFs in TPTD-treated group vs. 8 in non-TPTD group). The mean time to bone union was shorter in the TPTD-treated group (4.4 vs. 6.2 months; P =0.116), and union rate within 6 months was also higher in the TPTD-treated group (75% [6/8] vs. 50% [4/8]; P =0.3) achieved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All TPTD group showed fast er healing time (5.4±1.5 vs. 8.6±4.7 months; P =0.012), and low frequency of delayed healing or nonunion ( P =0.012) [ 61 ]. Yeh et al [ 62 ] also retrospectively examined 13 female patients with a total of 16 AFFs that all treated with an intramedullary fixation and divided into 2 groups (8 AFFs in TPTD-treated group vs. 8 in non-TPTD group). The mean time to bone union was shorter in the TPTD-treated group (4.4 vs. 6.2 months; P =0.116), and union rate within 6 months was also higher in the TPTD-treated group (75% [6/8] vs. 50% [4/8]; P =0.3) achieved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, a previous report has described the usefulness of teriparatide in the treatment of atypical femoral fractures [ 24 ]. Yeh WL, et al reported that the majority of patients (75%) treated with teriparatide treatment could achieve bone union within 6 months, with a mean time period of 4.4 months [ 25 ]. Moreover, a previous case report has described an additive effect of teriparatide and LIPUS during fracture healing [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not use teriparatide treatment for the reversal of the bisphosphonate effect because evidence is still lacking. Some reports suggest their use in bone healing, but an actual comparison with or without teriparatide treatment is not yet available [14]. Fortunately for our patient, we were still able to attain union by only the fixation of the fracture site with intramedullary devices.…”
Section: Discussionmentioning
confidence: 89%